Conceptualization, Design And Erection Of A Small Scale Cable-Dome Structure - Chai, Chen Chu (Universiti Sains Malaysia, 2006)
The main objective of this project is to gain insight about the design and erection sequence of cable-dome structures. Basic formulation of the analysis to determine self-equilibrium stress mode for cabled dome structure is first introduced. Analyses have been carried out on four different models. Design based on output obtained from analysis is then shown. Based on the design, appropriate amount of pre-tension to members of cable dome structure have been studied by means of actual construction of three mini-scale models and one trial model of 3 m span. The sequence of pre-tensioning process is also observed and shown.